The Potential of Artificial Intelligence in Developing Cultural Context of English Learning Materials: A Review Study - Rahmatillah Rahmatillah; Pebrina Nurwahyuningsih; Nana Erna; Nurianti H.S (Hasanuddin University, 2025)
English learning materials in Indonesia need to be designed to be more contextual and aligned with students' local culture, so that teaching materials can be more easily understood and increase their participation in learning. Unfortunately, the learning materials that integrate the sub-regions’ cultures, which reflect the provinces in which the learners learn, are infrequently developed. This gap makes it difficult for students to comprehend the materials since it is not related to their daily life experiences and their local regions. Meanwhile, the potential benefits offered by AI are very promising in developing culturally based materials in EFL context. This study aims to investigate the potential of AI in developing cultural context EFL materials. Through a comprehensive literature review, this study analyzed the literatures from the last five years, focusing on the importance of local culture in English learning materials and the potential use of AI in creating English teaching resources. The results showed that integrating local culture through AI addresses the gap between global-context materials and student needs, making learning more relevant and increasing motivation. Nonetheless, challenges such as cultural bias need to be carefully addressed, as AI may reinforce stereotypes and ignore the richness of local cultural diversity, potentially leading to misrepresentation or discrimination. Therefore, educators must be cautious in using AI to ensure that the materials produced accurately and effectively represent local culture.